398PPlanning for future cancer control programs in Uganda: Projections of top five cancers' incidence in the next decade. (24th November 2019) - Asasira, J; Mai, T X; Lee, S; Wabinga, H; Chang, Y; Jung, S-Y; Cho, H
Abstract: Background: Projections of the national burden of cancer are essential for planning cancer control programs and anticipating future cancer burden on the health service. This study aims to evaluate the current trend and project cancer incidences of the top five cancers in Uganda: Kaposi sarcoma (KS), cervical, breast, prostate, and Non-Hodgkin's lymphoma (NHL). Methods: Projections were based on incidence data obtained from the population-based Kampala cancer registry for the 2000-2014 periods, and population data was acquired from the National Bureau of Statistics. Joinpoint software was used to study the trend and presented results using age-specific rates, age-standardized rates, crude rates, and annual percentage change. Two methods were applied to project incidence up to 2029. First, we extrapolated results of the recent trend from joinpoint model to estimate future incidence with the assumption that coefficient estimates will remain constant. Second, we fitted the age-period-cohort model using Nordpred R-package, which accounts for age, period-birth cohort effects, rates were standardized using the standard world population (WHO 2000-2025). Results: Breast, cervical, and prostate cancer incidences are forecasted to increase by 2029. Their new cases are expected to increase by 200.5%, 98.7% and 184.3 % respectively with the ASRs (per 100, 000) escalating from 30.9, 51.9, 44.9 in 2000-2004 to 40.8, 52.7, 64.3 in 2025-2029. Incidences of KS and NHL are, on the other hand, anticipated to decrease for both males and females with both projection methods showing the same results. From 2000 to 2029, the ASR is expected to decrease markedly from 30.3 to 6.1 for KS and from 7.3 to 2.4 for NHL. The reduction in the number of cases is predominantly attributed to the change in their risk. The incidence rates were at peak among people aged from 65 to 74 for breast, cervical, prostate cancers, and those above 75 years for KS and NHL in the observed period. These patterns are expected to remain unchanged in the next decade. Conclusions: Future research should be directed towards strategies to control the growing burden of breast, cervical, and prostate cancers since their incidence rates are forecasted to increase in the future according to our study. Legal entity responsible for the study: Asasira Judith. Funding: "International Cooperation & Education Program (#NCCRINCCI 52210-52211, 2019)" of National Cancer Center, Korea. Disclosure: All authors have declared no conflicts of interest.